Multivalorisation et patrimonialisation de paysages d’arbres hors forêt en Ariège - Sylvie Guillerme; Jean-Paul Métailié; Éric Maire (Projets de Paysage)
As the heritage of rural systems which have used the tree as a structuring element, landscapes with non-woodland trees are under threat and are rarely taken into consideration in public policies. Yet they are of environmental and political importance not only due to the problems and challenges they present but also because of their potential, namely in terms of ecosystemic services. This type of tree cultivation historically contributed to plant and landscape diversity. The non-woodland tree has always been a component of very ancient agrarian systems. These landscapes which ensure biodiversity, also represent a cultural heritage dimension taken into account in local development policies. Focusing on the département of Ariège in the context of the closure of nature areas, the article addresses the dynamics and representations of landscapes with non-woodland trees, the role of these landscapes in public policies and regional development projects, as well as challenges regarding the conservation and valorisation of tree systems economically and ecologically marginalised.